2022
DOI: 10.1186/s12888-022-04007-w
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I converting enzyme gene polymorphisms and risk of psychiatric disorders

Abstract: Angiotensin-converting enzyme (ACE) as an important enzyme in the renin-angiotensin system facilitates biogenesis of the functionally active product angiotensin II from angiotensin I. ACE gene contains a number of functional polymorphisms which modulate activity of the encoded protein. In the current case–control study, we appraised the association between the rs4359 and rs1799752 polymorphisms and risk of bipolar disorder (type I and type II; BPDI and BPDII), schizophrenia (SCZ) and obsessive–compulsive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Conversely, other studies have also found evidence that carrying at least one D‐allele provides protection against SCZ, either generally (Crescenti et al, 2009) or specifically in women (Mazaheri & Saadat, 2015), while this polymorphism was not associated with SCZ in a Croatian population, but with a significant impact of the polymorphism on the clinical expression of the illness (Nadalin et al, 2012). Additionally, one study found the ACE I/D polymorphism to be associated with onset of SCZ, obsessive–compulsive disorder, BD type I and type II, suggesting that this ACE functional polymorphism can be regarded as a risk factor for a variety of psychiatric disorders (Akbari et al, 2022).…”
Section: Ace and Ace2 In Disorders Of The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have also found evidence that carrying at least one D‐allele provides protection against SCZ, either generally (Crescenti et al, 2009) or specifically in women (Mazaheri & Saadat, 2015), while this polymorphism was not associated with SCZ in a Croatian population, but with a significant impact of the polymorphism on the clinical expression of the illness (Nadalin et al, 2012). Additionally, one study found the ACE I/D polymorphism to be associated with onset of SCZ, obsessive–compulsive disorder, BD type I and type II, suggesting that this ACE functional polymorphism can be regarded as a risk factor for a variety of psychiatric disorders (Akbari et al, 2022).…”
Section: Ace and Ace2 In Disorders Of The Brainmentioning
confidence: 99%
“…Several studies have explored the association between the ACE gene I/D polymorphism and BD leading the authors to recognize that further studies are still necessary to confirm this association, in which a meta‐analysis suggested a possible association at least in Asian populations (Zou et al, 2011). Another ACE polymorphism, rs4359, was associated with risk of BD (both type I and type II) as well as obsessive–compulsive disorder, in co‐dominant and dominant models (Akbari et al, 2022).…”
Section: Ace and Ace2 In Disorders Of The Brainmentioning
confidence: 99%
“…Other polymorphisms can be much larger, involving longer stretches of DNA (Collins, Brooks, & Chakravarti, 1998). The genetic polymorphism present in the human genome has been linked to a variety of diseases (Akbari, Badrlou, et al, 2022;Ghafouri-Fard et al, 2022;Hussen et al, 2021;Qader et al, 2021;Taheri et al, 2022) such as psychiatric disorders (Akbari, Eghtedarian, et al, 2022). Recent developments in neurocriminology have revealed new aspects, including the possibility of genetic influences on violent criminal conduct (Coppola, 2018).…”
Section: Introductionmentioning
confidence: 99%